The Association Between Self‐Leadership and Nursing Professional Values Among Nursing Interns in China: A Cross‐Sectional Study - Wang Xuan; Xiang Cui; Liang Ting; Gou Li (International Nursing Review, 2026)
ABSTRACT Aim To describe nursing professional values among nursing interns in China and examine the association between self‐leadership and these values. Background Nursing interns are an essential part of the future nursing workforce, and the development of professional values during internships supports ethical practice and high‐quality patient care. Self‐leadership, a self‐regulatory process that guides motivation and behaviour, has been increasingly recognised as a resource for professional development. However, evidence on its relationship with nursing interns’ professional values remains limited. Methods We conducted a cross‐sectional survey at a tertiary general teaching hospital in China. Participants completed a general information questionnaire, the Chinese versions of the Revised Self‐Leadership Questionnaire (RSLQ) and the Nurses Professional Values Scale–Revised (NPVS‐R). Associations were examined using Pearson's correlation and multiple linear regression analyses. Results The mean total NPVS‐R score among the 374 nursing interns was 96.36 ± 16.38. Pearson's correlation analysis showed a significant positive correlation between self‐leadership and nursing professional values among nursing interns ( r = 0.435, p < 0.001). Multiple linear regression analysis showed that gender ( B = 0.254, p = 0.002), participation in nursing‐related academic activities ( B = −0.148, p = 0.021), and self‐leadership ( B = 0.427, p < 0.001) were significantly associated with nursing interns’ professional values. The model accounted for 23.2% of the variance (adjusted R 2 = 0.232). Conclusion The findings suggest that nursing interns with stronger self‐leadership may be more inclined to reflect on professional expectations and align their behaviour with professional values during clinical placement. Activism‐related professional values received comparatively lower ratings. Self‐leadership was positively associated with nursing interns’ professional values and may warrant further investigation in internship education and support. Implications for Nursing Practice‐based self‐leadership activities, preceptor coaching, and mentored professional socialisation could be explored in future research on nursing internship education. Implications for Health Policy At the organisational and policy levels, the findings may inform future evaluation of approaches involving internship standards, structured mentorship, and clinical learning environments.